The Situation of the National Music Curriculum Implementation: what do the Arts Maturity Examination Results Reveal - Jautakytė, Žydrė (Pedagogika, 2015)
After the restoration of Lithuanian independence, since 1994 the preparation of the national curriculums for general education schools started. However, through this period the actual situation of the national music curriculum implementation has been explored to a limited extent. As the awareness of the importance of an evidences and data to the formation and creation of the education content is notably growing nowadays, it is important to collect various data about the actual situation of music education on purpose to improve it. In this article the results of the analysis of the arts maturity examination works in the music field are introduced and some generalized propositions are given about the actual situation of music education and the emerging fields of the music education practice, which are problemic or need to be improved. Research aim is to describe the situation of Lithuanian national music curriculum implementation on the ground of an analysis of student’s art maturity examination works in the music field. Research method is analysis of pedagogical literature, education documents and content of student’s art maturity examination works in musical field. Research organization and results. Since 2013 a new arts maturity examination has been implemented, which has a music direction and is a long-term task, consisting of these examined parts: a creative process, an art work (an interpretation of music works or the musical production), description of creative work and its presentation. National examination center, which coordinates the implementation of examination, under its determinate order has selected and presented 43 works of music interpretation and 10 works of musical production for the analysis, while the total number of performed works is 241. The material for analysis consisted of the description of a creative work (scanned variant of an original text), audio and video recordings of presentations of creative works. Material was analyzed on the grounds of examination evaluation criteria. When analysis was done, the generalized propositions of fulfilment to criteria in student works were presented and they also were compared to the national music curriculum provisions and the parallels with its implementation situation were drawn. Analysis of 30 video recordings of music interpretation examination, in which students performing their prepared program were recorded, has shown that 19 of them have chosen works that does not correspond to their abilities, i. e. are too difficult or too easy. Only 9 of these works show an original interpretation. It emerged that those students who have demonstrated the interpretation abilities while implementing an exam program, in the creative work description have also gone deep to the nuances of the style, genre and work’s impressiveness and have described their conception on the grounds of analysis of works’ texts and context. With reference to the analysis of 43 descriptions of creative works it is possible to state that only 5 of them fully correspond to criteria. Analyzed descriptions revealed that students’ capacities to analyze musical works, explore context and use concepts purposefully are not explicit. It was quite difficult for the students to formulate the idea and conception of a creative work and to use data of the context exploration to describe their project. Also the mistakes of general writing rules, grammar, style, selection and generalization of information and citation were noticed. From 10 analyzed musical composition 5 students’ works can be evaluated as excellent, they fully corresponds to the examination evaluation criteria. 3 works are weak, they could not be characterized as authentic works. It was discovered that students, who have chosen an examination in musical creation field, were inspired by their own experience and that music lessons have had a little influence on their choice. Half of the students, who have chosen this direction, has demonstrated very good results of both creative work and description writing.